(untitled) (Fiep Bulletin - online, 2017)
The Early Childhood Education is considered the primary step towards the acquisition of knowledge and has the function to fully form the child, so it is essential to the social function of physical education teacher at that stage. In this regard, the paper aims to bring some reflections on the power of games and play as a pedagogical possibility for the development of physical education. So a systematic review about the contribution of games and play in early childhood education Physics was held. The consensus discussion unveiled by the existing theoretical contribution is that the games and the games are an integral part of children’s culture and use them as a pedagogical possibility can be a powerful tool for teaching and learning.